Same Dosages of rPRV/XJ5-gI−/gE−/TK− Prototype Vaccine or Bartha-K61 Vaccine Similarly Protects Growing Pigs Against Lethal Challenge of Emerging vPRV/XJ-5 Strain - Ren, Qinghai; Li, Lin; Pan, Haochun; Wang, Xiaobo; Gao, Qingqing; Huan, Changchao; Wang, Jin; Zhang, Wei; Jiang, Luyao; Gao, Song; Kai, Yan; Chen, Changhai (Frontiers in Veterinary Science, 2022)
Variant pseudorabies viruses (vPRV) have constantly emerged in China since late 2011. In the present study, a 1 × 106.0 TCID50 per-animal dosage of a commercially available BarthaK61 vaccine and an rPRV/XJ5gI−/gE−/TK− prototype vaccine freshly extracted from the vPRV/XJ5 at the same dose were administered to evaluate the immune effectiveness thereof on growing pigs to prevent lethal strikes caused by vPRV/XJ5. The results suggest that the BarthaK61 vaccine at a dose of 1 × 106.0 TCID50 per animal and the same dosage of the rPRV/XJ5gI−/gE−/TK− prototype vaccine protected growing pigs against the lethal challenge of vPRV/XJ5 strain with 100% survive rate. Furthermore, the outcome of the clinical score, virus shedding, weight gain, and viral loads in different pig tissues in these two groups demonstrates that either the BarthaK61 vaccine or the rPRV/XJ5gI−/gE−/TK− prototype vaccine at the same dose exhibited parallel efficacy in pigs against the lethal challenge with the XJ5 strain of vPRV.